1998
DOI: 10.1139/o99-008
|View full text |Cite
|
Sign up to set email alerts
|

Odontoblast commitment and differentiation

Abstract: Histological and cytological organization confer specificity to the odontoblasts. These postmitotic, neural crest derived, polarized cells are aligned in a single layer at the periphery of the dental pulp and secrete the organic components of predentin-dentin. The developmental history of these cells demands a cascade of epigenetic signalling events comprising the acquisition of odontogenic potential by neural crest cells, their patterning in the developing jaws, the initiation of odontogenesis through interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
340
1
17

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(363 citation statements)
references
References 88 publications
5
340
1
17
Order By: Relevance
“…The differentiation starts from the cusp tips and proceeds downward to cervical and intercuspal directions. Signals in Tgfb/Bmp families have been implicated in odontoblast induction (Ruch et al 1995), and it was shown recently that the conditional loss of Smad4, a mediator of Tgfb/Bmp signaling, from the dental papilla prevents the terminal differentiation of odontoblasts and dentin deposition (Li et al 2011a). As the formation of enamel knots is temporally associated with the initiation of odontoblast differentiation at the cusp tips, the enamel knot signals have been suggested to play a role (Fig.…”
Section: Signaling Network Regulating Tooth Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The differentiation starts from the cusp tips and proceeds downward to cervical and intercuspal directions. Signals in Tgfb/Bmp families have been implicated in odontoblast induction (Ruch et al 1995), and it was shown recently that the conditional loss of Smad4, a mediator of Tgfb/Bmp signaling, from the dental papilla prevents the terminal differentiation of odontoblasts and dentin deposition (Li et al 2011a). As the formation of enamel knots is temporally associated with the initiation of odontoblast differentiation at the cusp tips, the enamel knot signals have been suggested to play a role (Fig.…”
Section: Signaling Network Regulating Tooth Developmentmentioning
confidence: 99%
“…The localization of Wnt reporter activity in odontoblasts is also in line with the role of Wnts in the process . In addition, the basement membrane is important for the polarization and differentiation of the odontoblasts and serves presumably as a reservoir of signal molecules (Thesleff and Hurmerinta 1981;Ruch et al 1995). Dentin is composed mainly of type I collagen, dentin phosphoprotein, and Dspp, and mutations in these genes cause dentinogenesis imperfecta in humans (Shields et al 1973).…”
Section: Signaling Network Regulating Tooth Developmentmentioning
confidence: 99%
“…After tooth eruption, reparative dentin is formed by odontoblasts in response to general mechanical erosion or disruption, and through dentinal degradation caused by bacteria (2). These odontoblasts are thought to arise from the proliferation and differentiation of a precursor population, residing somewhere within the pulp tissue (3). Despite extensive knowledge of tooth development, and of the various specialized tooth-associated cell types, little is known about the characteristics and properties of their respective precursor cell populations in the postnatal organism.…”
mentioning
confidence: 99%
“…Dental pulp tissue contains a heterogeneous population of cells that include dentin-forming odontoblasts, fibroblasts, neurons, and cells of the vascular and immune systems [1,2]. Histologically, dental pulp is organized in zones.…”
Section: Introductionmentioning
confidence: 99%